2015
DOI: 10.1016/j.jtcvs.2015.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of digital versus analog pleural drainage in patients with or without a pulmonary air leak after lung resection

Abstract: Although digital devices decreased tube clamping trials, the impact on duration of chest tube drainage and hospital stay was not statistically significant, even after stratifying by postoperative air leak status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 14 publications
3
68
0
1
Order By: Relevance
“…These results were reproduced in a multicenter international trial, which showed that patients managed with digital drainage systems had a shorter chest tube duration, shorter hospital stays, and significantly higher satisfaction scores when compared with those managed with traditional methods [8]. On the contrary, there were randomized trials showing that digital drainage systems did not reduce chest tube duration or length of hospitalization significantly compared with traditional water-sealed analog drainage systems [12][13][14][15]. Nevertheless, Gilbert and colleagues showed that the use of digital drainage systems significantly reduced the number of clamping attempts before the removal of the last remaining chest tube, indicating that the objective air leak trend data by the technology may serve as a more sensitive and reliable tool and may be clinically useful information [15].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results were reproduced in a multicenter international trial, which showed that patients managed with digital drainage systems had a shorter chest tube duration, shorter hospital stays, and significantly higher satisfaction scores when compared with those managed with traditional methods [8]. On the contrary, there were randomized trials showing that digital drainage systems did not reduce chest tube duration or length of hospitalization significantly compared with traditional water-sealed analog drainage systems [12][13][14][15]. Nevertheless, Gilbert and colleagues showed that the use of digital drainage systems significantly reduced the number of clamping attempts before the removal of the last remaining chest tube, indicating that the objective air leak trend data by the technology may serve as a more sensitive and reliable tool and may be clinically useful information [15].…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, digital drainage systems have become a useful adjunct to clinical management [11]. However, the benefit of digital drainage systems has been a debate in the literature, and trials have shown conflicting results [7,8,[12][13][14][15]. In a prospective randomized study, the digital device protocol, in which chest tube removal was based on digitally recorded measurements, was compared to the traditional analog protocol, in which chest tube removal was based on an instantaneous assessment of air leak during daily rounds.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the world-wide experience published in the English scientific literature remains limited with less than 1,000 cases of anatomic lung resection (2,(5)(6)(7)(8)(9)(10)(11)(12). Our general approach to the introduction of new surgical techniques or technology into clinical practice has emphasized safety and efficacy by carefully recording and analyzing outcomes (13,14). It is only very recently that other comparative studies of multiple port and single port lung resection have started to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a multicenter prospective randomized trial comparing digital monitoring using the Thopaz system to a traditional thoracic drainage system in 381 patients who underwent segmentectomy or lobectomy, Pompili and colleagues 9 reported that patients managed with the Thopaz system experienced a shorter duration of chest tube placement and shorter hospital stay compared with those managed with traditional devices. By contrast, Gilbert and colleagues 16 reported no statistically significant differences in the duration of chest tube drainage or hospital stay in both a group of 87 patients without air leak and a group of 85 patients with air leak in their single-center prospective randomized trial. Lijkendijk and colleagues 17 also reported that the Thopaz system did not significantly reduce the duration of chest tube drainage or hospitalization compared with traditional water seal drainage.…”
Section: Discussionmentioning
confidence: 88%